Invitation to philosophy : issues and options - Honer, Stanley M. (Wadsworth, 2002)
Using an issues-and-options approach, in a handbook format, this text deals with each major topic in philosophy by using a succinct, relevant, and readable presentation and critique of the representative options (e.g., schools of thought, individual philosophers) within each topic. A continuum helps students see the options available to answer a variety of basic questions and the relationship each option has to the others. The options found on the continuum are discussed and followed by a case study drawn from contemporary life that helps students to apply the options.